A Comperative Study Between Using Video and Audio as Media in Students’ Listening Comprehension at the Eighth Grade of SMPN 30 Sijunjung - Nofrianti, Monika; Dewi, Merry Prima; Irwandi, Irwandi; Syafitri, Widya (Education Achievement: Journal of Science and Research, 2024)
This study was conducted to address the issues observed in SMPN 30 Sijunjung. The identified issues were students' tendency to complan. when the teacher did not provide further explanation in Bahasa during audio activities, difficulty in comprehending native speakers due to their fast pace, lack of focus during video or movie-based listening activities, and confusion regarding certain vocabulary. The aim of this research is to compare the effectiveness of using video and audio as media in students' listening comprehension.A quantitative research approach was utilized in this study. The design was comparative with VIII.1 and VIII.2 as the sample classes, each taught using either video or audio. The data was collected through a listening test.Based on the data gathered from the eighth grade students of SMPN 30 Sijunjung, it was concluded that there is no significant difference in the overall scores of students' listening comprehension when using video or audio. However, the findings showed variations in specific listening skills, with the video group performing better in distinguishing sounds and the audio group excelling in decoding verbal messages. Additionally, both groups had similar levels of ability in perceiving and retaining the entire message. These results suggest that both video and audio can equally facilitate students' listening comprehension.